System interoperability as a factor for the development of research repositories in scholarly communication - Kuprienė, Jūratė; Prokopčik, Marija; Petrauskienė, Žibutė (Information & Media, 2017)
It is evident that the speed of scholarly communication goes up tendentious if research products are communicated via social networking platforms. Researchers use the functionality of these platforms without any difficulties and get means for the fast spread of their achievements and for finding research partners. Speed, flexibility and simplicity become the essential conditions for information infrastructure products if there is an intention to reach the leading position in the market. The unquestionable priority of scholarly communication platforms in Lithuania is given to Web of Science, Scopus, ScienceDirect. Nevertheless, a breakthrough is seen in the global permanent identifiers for researchers in ResearcherID and ORCID, the global social networking platforms for researchers ResearchGate and Academia.edu or other. The progress of these products is ensured through the flexible functionality provided with precise insights into the needs of researchers, and it is realized through the interoperability of various information systems. This phenomenon is relevant to the development of the Lithuanian national information system eLABa. This paper presents the research made to examine the factors of scientific communication that recently leads to the future developments of eLABa repository. Results of this research indicate the duplication of data preparation, supply and preservation processes, too, and suggest the interoperability between the systems and processes of the Research Council of Lithuanian, the Research and Higher Education Monitoring and Analysis Center, the national data archive MIDAS, systems of research institutions, the Center of Information Technologies in Education, Claritative Analytics Web of Science, Scopus, DOAJ, SherpaRomeo, Creative Commons, ResearchGate, Academia.edu, ORCID and Google Scholar and The Data Bank of National Bibliography.
Keywords: ...